Consultation bulletin and technical service contents for Quest magazine July-December 2015 - IBM Centre of Excellence, (IBM CoE) (Penerbit UMP, 2015)

(untitled)
Cloud Service for MyGrants System- MyGrant Portal System is an information platform relating to DPF - a system which comprises the schedule for grant opening, guideline and networking. IBM CoE is appointed to carry out maintenance work of MyGrants System for 2015 and putting the Service Project as one of the contract researches in Universiti Malaysia Pahang.